The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bbmt.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between an Impaired Bone Marrow Vascular Microenvironment and Prolonged Isolated Thrombocytopenia after Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Prolonged isolated thrombocytopenia (PT) is a serious complication after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, it remains unclear whether abnormalities of the bone marrow (BM) microenvironment are involved in the pathogenesis of PT. This prospective, nested case-control study included 20 patients with PT, 40 matched patients with good graft function (GGF) after allo-HSCT, and 16 healthy donors (HDs). Cellular elements of the BM microenvironment, including BM endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 45 publications
2
57
1
Order By: Relevance
“…The gating strategies used for perivascular cells and bone marrow endothelial cells were previously reported 2,15 and are shown in Figure 1. An aliquot of 5 ml of fresh bone marrow was stained with mouse antihuman CD146-PE/CD34-PECy7/CD45-V500/vascular endothelial growth factor receptor 2 (VEGFR2) Alexa fluor 647-conjugated monoclonal antibodies (Becton Dickinson, San Jose, CA, USA).…”
Section: Immune Phenotypingmentioning
confidence: 99%
See 3 more Smart Citations
“…The gating strategies used for perivascular cells and bone marrow endothelial cells were previously reported 2,15 and are shown in Figure 1. An aliquot of 5 ml of fresh bone marrow was stained with mouse antihuman CD146-PE/CD34-PECy7/CD45-V500/vascular endothelial growth factor receptor 2 (VEGFR2) Alexa fluor 647-conjugated monoclonal antibodies (Becton Dickinson, San Jose, CA, USA).…”
Section: Immune Phenotypingmentioning
confidence: 99%
“…Immune histochemistry staining was performed using rabbit anti-human osteopontin, CD34 and CD146 primary antibodies (Abcam, Cambridge, MA, USA) as previously described. 2,15 The slides were read blindly by two observers. Each section was analyzed using light microscopy (Axiovert 200; Carl Zeiss, Jena, Germany).…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…The delay in platelet recovery or prolonged isolated thrombocytopenia remains the main problem of hematopoietic reconstitution after unmanipulated haplo-HCT. 19 Although its mechanism is not clear, choosing a younger donor from the haploidentical family members should be preferred. 20 In allo-HCT from matched sibling donors, trials have shown a significantly higher incidence of acute GvHD grade 2-4, 6,7 chronic GvHD and extensive chronic GvHD 6,20 in PBSC recipients compared with BM recipients.…”
Section: Discussionmentioning
confidence: 99%